The dynamics of reform of India's federal system - Nirvikar Singh (University of California, Economics Department, 2007)
This paper analyzes the process of reform of India's federal system, with a focus on fiscal federalism. We first summarize the basic features of, and recent reforms in intergovernmental relations, including the role of political institutions, assignments of expenditure responsibility and revenue authority, the system of intergovernmental transfers, and institutions and mechanisms for government borrowing. We then discuss the institutional specifics of the reform process, to understand the dynamics of India's federal system.
Keywords: P26; P35; H1; H7; 330; federalism; decentralization; intergovernmental relations; economic reform; Föderalismus; Reform; Indien